Combined Clinical, Epidemiological, and Genome-Based Analysis Identified a Nationwide Outbreak of Burkholderia cepacia Complex Infections Caused by Contaminated Mouthwash Solutions - Bender, Jennifer K.; Haller, Sebastian; Pfeifer, Yvonne; Hogardt, Michael; Hunfeld, Klaus-Peter; Thuermer, Andrea; Zanuzdana, Arina; Werner, Markus; Kunz, Bernd; Eisenberger, David; Pfennigwerth, Niels; Kempf, Volkhard A. J.; et al. (Open Forum Infectious Diseases, 2022)
Background In September 2018, Burkholderia cepacia complex (BCC) infections in 3 patients associated with exposure to a mouthwash solution (MWS) were reported to the Robert Koch Institute (RKI). As the product was still on the market and the scale of the outbreak was unclear, a nation-wide investigation was initiated. Methods We aimed to investigate BCC infections/colonizations associated with MWS. Hospitals, laboratories, and public health services were informed that BCC isolates should be sent to the RKI. These isolates were typed by pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS) including development of an ad hoc core genome MLST (cgMLST) scheme. Results In total, 36 patients from 6 hospitals met the case definition, the last patient in November 2018. Twenty-nine isolates from 26 of these patients were available for typing. WGS analysis revealed 2 distinct cgMLST clusters. Cluster 1 (Burkholderia arboris) contained isolates from patients and MWS obtained from 4 hospitals and isolates provided by the manufacturer. Patient and MWS isolates from another hospital were assigned to cluster 2 (B. cepacia). Conclusions The combined clinical, epidemiological, and microbiological investigation, including whole-genome analysis, allowed for uncovering a supraregional BCC outbreak in health care settings. Strains of B. arboris and B. cepacia were identified as contaminating species of MWS bottles and subsequent colonization and putative infection of patients in several hospitals. Despite a recall of the product by the manufacturer in August 2018, the outbreak lasted until December 2018. Reporting of contaminated medical products and recalls should be optimized to protect patients.
CRIS-Team WoS Importer:2022-04-29
Keywords: Burkholderia arboris; outbreak; clonal transfer; mouthwash solution; medical device

Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Valenza, Giuseppe; Eisenberger, David; Voigtländer, Sven; Alsalameh, Rayya; Gerlach, Roman; Koch, Sonja; Kunz, Bernd; Held, Jürgen; Bogdan, Christian (Microbiology Spectrum, 2023)
IMPORTANCE: The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015-2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.
CRIS-Team Scopus Importer:2023-12-29
Keywords: bloodstream Infection; core genome multilocus sequence typing; Enterococcus faecium; ST1299 vanA; vancomycin resistance

Homologous COVID-19 BNT162b2 mRNA Vaccination at a German Tertiary Care University Hospital: A Survey-Based Analysis of Reactogenicity, Safety, and Inability to Work among Healthcare Workers - Niekrens, Valentin; Esse, Jan; Held, Jürgen; Knobloch, Carina; Steininger, Philipp; Kunz, Bernd; Seggewies, Christof; Bogdan, Christian (Vaccines, 2022)
At the start of the SARS-CoV-2 pandemic, healthcare workers had an increased risk of acquiring coronavirus disease (COVID)-19. As tertiary care hospitals are critical for the treatment of severely ill patients, the University Hospital Erlangen offered BNT162b2 mRNA vaccination against COVID-19 to all employees when the vaccine became available in Germany. Here, we performed a survey to assess the age- and sex-dependent reactogenicity and safety of BNT162b2 in a real-life setting with a special emphasis on the rate of vaccine-related incapacity to work amongst the employees. All vaccinated employees were invited to participate in the survey and received access to an electronic questionnaire between 31 March and 14 June 2021, which allowed them to report local and systemic adverse effects after the first or second vaccine dose. A total of 2372 employees completed the survey. After both the first and second dose, women had a higher risk than men for vaccine-related systemic side effects (odds ratio (OR) 1.48 (1.24-1.77) and 1.49 (1.23-1.81), respectively) and for inability to work (OR 1.63 (1.14-2.34) and 1.85 (1.52-2.25), respectively). Compared to employees >= 56 years of age, younger vaccinated participants had a higher risk of systemic reactions after the first (OR 1.35 (1.07-1.70)) and second vaccination (OR 2.08 (1.64-2.63)) and were more often unable to work after dose 2 (OR 2.20 (1.67-2.88)). We also recorded four anaphylactic reactions and received two reports of severe adverse effects indicative of vaccine complications. After the first and second vaccination, 7.9% and 34.7% of the survey participants, respectively, were temporarily unable to work, which added up to 1700 days of sick leave in this cohort. These real-life data extend previous results on the reactogenicity and safety of BNT162b2. Loss of working time due to vaccine-related adverse effects was substantial, but was outweighed by the potential benefit of prevented cases of COVID-19.
CRIS-Team WoS Importer:2022-06-10

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

SOP – Umgang mit multiresistenten Erregern auf der Palliativstation - Ostgathe, Christoph; Stachura, Peter; Hofmann, Sonja; van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Förtsch, Bärbel; Klein, Carsten (Onkologe, 2017)
CRIS-Team Scopus Importer:2024-02-26